Implicating factors in the increase in cases of central precocious puberty (CPP) during the COVID-19 pandemic: Experience of a tertiary centre of pediatric endocrinology and review of the literature - Barberi, C.; Di Natale, V.; Assirelli, V.; Bernardini, L.; Candela, E.; Cassio, A. (Frontiers in Endocrinology, 2022)
Sexual development is a complex mechanism activated by the hypothalamic-pituitary-gonadal axis. Over the last one hundred years there has been a decline in the age at puberty onset in industrialised countries. Some Italian studies showed an increase in diagnoses of Central Precocious Puberty (CPP) during the COVID-19 pandemic. It is thus supposed that in this period there was an increased impact of factors that can influence pubertal development. Our retrospective monocentric study aimed to confirm the existence of this phenomenon and analysed possible related factors. We retrospectively evaluated clinical, laboratory, radiological and ultrasound (US) data of 154 girls referred to our Tertiary Centre of Paediatric Endocrinology from January 2019 to April 2021 for different forms of Precocious Puberty. We subdivided the cases into subgroups according to the final diagnosis: CPP, Early Puberty (EP) , isolated thelarche and isolated pubarche. The observation period was subdivided into: Period 1, before lockdown (1 January 2019 – 8 March 2020) and Period 2, lockdown and the following months (9 March 2020 – 30 April 2021). Period 2 was further divided into “restrictive lockdown period” (Period 2.1) (March 2020 – 14 June 2020, in which the schools were closed) and “less restrictive lockdown period” (Period 2.2) (15 June 2020 – 30 April 2021). We analysed data regarding the use of electronic devices before and during lockdown in a group of girls with CPP diagnosed in Period 2 and we compared the data with that of a control group. Our data show an increase in the number of new diagnoses of CPP during lockdown and in the following months, compared with the previous period. We also detected a higher use of PCs and smartphones in girls with CPP diagnosed in Period 2, compared with the control group. The percentage of the presence of endometrial rhyme detected during the pelvic ultrasound was higher in girls with CPP in Period 2, compared with the previous period. We assume there was an environmental effect on pubertal timing that calls our attention to factors such as food, use of electronic devices and stress.